Valeur du témoignage et du code chez N. Scott Momaday - Anne Garrait-Bourrier (Revue LISA)
Scott Momaday is a Kiowa-born American writer. As a storyteller, he conveys through his writing his own Indian heritage. To do so he uses varied generic forms such as poetry, painting and autobiographical narratives. What he actually conveys, more than this mythical and traditional background, is a very original and genuine mode of writing, a new literary genre based on codes to be deciphered. Momaday’s text can be read through different angles: the mythical one, the classical anglo one, and a more personal and unifying approach rooted in the imagination of the writer himself.